Advancements in Nanoparticle-Based Precision Drug Delivery: A Review of Development and Optimization for Targeted Therapy in Preclinical Models - Nikandish, Mehrasa; Wang, Hanzhi; Bao, Xinqi; Nikandish, Mohamad (European Scientific Journal, ESJ, 2024)
In recent years, the widespread adoption of nanoparticles has expanded across a broad spectrum of clinical domains. These nanoparticles have been specifically engineered to address the limitations associated with conventional therapeutics and to navigate various biological barriers—ranging from systemic to cellular levels—that manifest heterogeneity across different patient populations and disease states. The advent of precision treatments, wherein interventions are tailored to individual patients, has contributed to mitigating this variability among patients. Nonetheless, the predominant focus in current nanoparticle research remains on enhancing the uniformity of delivery systems. The realization of precision medicine appears imminent as lipid-based, polymeric, and inorganic nanoparticles are increasingly crafted with heightened precision, facilitating more individualized approaches to medication delivery. In this review, we delve into the advanced designs of nanoparticles employed in both precision and generalized applications, offering insights into their potential to advance precision medicine. Our discussion centers on the innovations in nanoparticle design aimed at overcoming various delivery challenges, suggesting that ingenious nanoparticle engineering holds promise for enhancing performance across a broad spectrum of delivery applications and facilitating tailored designs for specific therapeutic targets, ultimately leading to improved patient outcomes.